Control interno de los procesos contables en el Gobierno Autónomo Descentralizado Provincial de Los Ríos correspondiente al periodo 2019 - Salvatierra Santillán, Elsa Priscila (2020)
Within both public and private organizations, in order to guarantee the development of activities, various control systems are applied to know how activities are developed; Within the financial department these controls are made with greater constancy and emphasis, knowing the financial statements of a company allows taking corrective and preventive measures and thus guaranteeing the profitability of each one of them. In the Autonomous Decentralized Provincial Government of Los Ríos, the various controls are applied, but it was identified that the institution does not correctly apply the internal control of accounting processes, which has triggered several problems that compromise the activities of the institution; Problems such as the lack of interest on the part of the authorities reflected in the non-application in the financial control systems, in addition to the fact that there are shortcomings with the collaborators, all this causes that an internal control system of accounting processes is not applied and this is see engaged; the risks that arise and that affect the achievements that the institution has proposed in consideration of the methodology approached that allows us to identify the different deficiencies that must be analyzed to improve the situation facing the entity and at the same time be able to detect and correct the deviations that compromise the objectives set by the administration based on the investigation reaching the interview that was carried out with the entity's accountant in order to have a direct observation of the phenomena that affect the entity.